Labor Market Performance Analysis of OECD Countries - Süheyla Erikli; Serap Pelin Türkoğlu (Sosyal Siyaset Konferansları Dergisi)
This article analyzed the labor market performance of 28 Organization for Economic Co-operation and Development (OECD) countries in 2018. The indicators of labor market performance were the unemployment rate, long-term unemployment rate, youth unemployment rate, youth not in employment, education or training (NEET) rate, employment rate, employment participation rate, part-time employment rate, and temporary employment rate. The method of multi-objective optimization on the basis of simple ratio analysis (MOOSRA) was used, which is one of the multi-objective decision-making methods. The entropy method was preferred to determine the weighting of the criteria. It was concluded that the most successful labor performance in the 28 countries examined was found in Iceland, the Czech Republic, and Estonia, and the worst performance was in Spain, Italy, and Greece.